Determinan Diabetes Mellitus Tipe 2 pada Usia Produktif di Wilayah Puskesmas Kecamatan Jagakarsa Jakarta Selatan Tahun 2022: Determinants of Type 2 Diabetes Mellitus in Productive Age in the Jagakarsa District Health Center Area, South Jakarta in 2022 - Noviyanti, Shabrina Rahmi; Nina; Dianti, Anggi Risma; Setiawaty, Savanna (MPI Press, 2023)
Background: The worldwide incidence of Diabetes Mellitus is around 171 million and is predicted to reach 366 million by 2030. Southeast Asia has 46 million people and is estimated to increase to 119 million. In Indonesia from 8.4 million in 2015 it is estimated to be 21.3 million in 2030. Objectives: This study aims to analyze the Determinants of Diabetes Mellitus in the South Jagakarsa District. Method: The population of this study is a community in the Puskesmas Jagakarsa area with a sample of 100 respondents who filled out online questionnaires using google Forms. The research was conducted in December–January 2022, with research types this research method, combines quantitative research most people at Puskesmas Jagakarsa are still many I’ve mixed methods using primary observation data using online questionnaires (google forms) and other data under Profile of the 2021 Jagakarsa Subdistrict Puskesmas. Result: Research results are known that most people at Puskesmas Jagakarsa are still many understand Type 2 Diabetes Mellitus disease (54%) with good grades and still many who are not good (48%). Conclusion: Prioritization of problem-solving is carried out using the matrix criteria method by taking into account the level of effectiveness and efficiency. The importance of educating the community in Jagakarsa District to be wise in choosing the food to be consumed, then an alternative solution to the main problem is obtained by outreach to people of productive age to disseminate health information about